GE_GERICHTE P/10239/2021 vom 14. August 2025 - GE Cour de justice (2025)
ORDONNANCE DE CLASSEMENT;USURE(DROIT PÉNAL);DÉNONCIATION CALOMNIEUSE;FAUX DANS LES CERTIFICATS | CPP.319; CP.157; CP.303; CP.251; LAVS.87.al4